Direct Pulmonary Vein Ablation With Stenosis Prevention Therapy. (16th August 2015) - DeSIMONE, CHRISTOPHER V.; HOLMES, DAVID R.; EBRILLE, ELISA; SYED, FAISAL F.; LADEWIG, DOROTHY J.; MIKELL, SUSAN B.; POWERS, JOANNE; SUDDENDORF, SCOTT H.; GILLES, EMILY J.; DANIELSEN, ANDREW J.; HODGE, DAVID O.; KAPA, SURAJ; et al.
Direct Pulmonary Vein Ablation With Stenosis Prevention Therapy Introduction The dominant location of electrical triggers for initiating atrial fibrillation (AF) originates from the muscle sleeves inside pulmonary veins (PVs). Currently, radiofrequency ablation (RFA) is performed outside of the PVs to isolate, rather than directly ablate these tissues, due to the risk of intraluminal PV stenosis. Methods In 4 chronic canine experiments, we performed direct PV muscle sleeve RFA ± postablation drug‐coated balloon (DCB) treatment with paclitaxel/everolimus. Of the 4 PVs, 2 PVs were ablated and treated with DCB, 1 PV was ablated without DCB treatment (positive control), and 1 PV was left as a negative control. Local electrograms were assessed in PVs for near‐field signals and were targeted for ablation. After 12–14 weeks survival, PVs were interrogated for absence of near‐field PV potentials, and each PV was assessed for stenosis. Results All canines survived the study period without cardiorespiratory complications, and remained ambulatory. In all canines, PVs that were ablated and treated with DCB remained without any significant intraluminal stenosis. In contrast, PVs that were ablated and not treated with DCB showed near or complete intraluminal stenosis. At terminal study, PV potentials remained undetectable. A blinded, histologic analysis demonstrated that ablated PVs without DCB treatment had extensive thrombus, fibrin, mineralization, and elastin disruption. Conclusion Our chronic canine data suggest that direct PV tissue ablation without subsequent stenosis is feasible with the use of postablation DCBs.